The Optimal Inventory Policy with the Reusable Raw Material and Imperfect Items - Shou-Mei Su; Chia-Jung Chou; Shy-Der Lin (International Journal of Supply Chain Management, 2014)
This paper covers four topics regarding inventory models, namely reusable raw material, the EPQ model, imperfect-quality items, and the present value method. The relevant cost value used in traditional EPQ models does not include the stockholding cost of raw material, which makes such models unsuitable for investigating production. Because people in the world are attempting to reduce the impact of environmental impairment and increasing market competition, all products are manufactured from 100% reusable raw material and are screened during the manufacturing process. By taking the fixed proportion of imperfect-quality items and the time value into account and applying the present value method to analyze optimal inventory policies, this study creates a modified EPQ inventory model that is close to real life we meet. Furthermore, this model aims to promote the reputation of a company and ascertain its costs accurately.